Evaluating Faculty Development and Clinical Training Programs in Substance Abuse A Guide Book - Klitzner, Michael; Stewart, Kathryn; Pacific Inst. for Research and Evaluation, Walnut Creek, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Intended to provide an overview of program evaluation as it applies to the evaluation of faculty development and clinical training programs in substance abuse for health and mental health professional schools, this guide enables program developers and other faculty to work as partners with evaluators in the development of evaluation designs that meet the specialized needs of faculty development and clinical training programs. Section I discusses conceptual issues in program evaluation, including the uses of evaluation (management and monitoring, program description, program improvement, accountability, and creating new knowledge); the major options (formative/summative, process/outcome/impact, quantitative/qualitative); and the benefits and risks of conducting evaluation studies. Section II, an introduction to research methods, includes the following discussions: sampling with known sampling errors (simple random, systematic, multistage random, stratified, cluster, stratified cluster, and sequential sampling); sampling without known sampling errors (convenience, quota, modal, purposive, and snowball sampling); sample size and generalizability and sample size and statistical power; the validity of evaluations and potential sources of bias, including issues related to internal validity (history, maturation, testing, instrumentation, statistical regression, selection, mortality, interactions with selection, and ambiguity about the direction of causal influence); comparison and control groups; measurement of outcomes; and qualitative evaluation methods and analysis. (5 references) (JB)
Sponsoring Agency: National Inst. on Drug Abuse (DHHS/PHS), Rockville, MD.
Sponsoring Agency: National Inst. on Alcohol Abuse and Alcoholism (DHHS), Rockville, MD.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alcohol Abuse; Allied Health Occupations Education; Clinical Teaching (Health Professions); Drug Abuse; Evaluation Methods; Faculty Development; Graduate Medical Education; Higher Education; Medical Education; Medical School Faculty; Mental Health; Program Evaluation; Qualitative Research; Research Methodology; Sampling; Statistical Bias; Substance Abuse; Guides, Non-Classroom.; Reports, Descriptive